Respon Pertumbuhan Tanaman Sawi (Brassica juncea L.) Akibat Pemberian Air Fermentasi Limbah Organik Cair - Novianti Novianti; Hayatul Rahmi (JURNAL AGROPLASMA, 2023)
Mustard greens is a vegetable that is in great demand by the public because it contains various good nutrients for health and its cultivation is easy to do, so to meet public demand it is necessary to increase production, namely by fertilizing.. This study aims to obtain the concentration of liquid organic waste fermented water which has the best effect on the growth of mustard greens (Brassica juncea L.). The research method used was a Single Factor Randomized Block Design (RBD) experiment with fermented water concentrations of liquid organic waste, namely A0 (control), A1 (100 ml/l), A2 (200 ml/l), A3 (300 ml/l) , A4 (400 ml/l), A5 (500 ml/l) and A6 (POC NASA 4 ml/l). Consists of 7 treatments and 5 replications, so there are 35 experimental units. The results of analysis of variance and DMRT level of 5% explained that the difference in the concentration of fermented liquid organic waste had a significant effect on plant height and number of leaves aged 14, 21 and 28 days after mustard plants. Treatment A1 (100 ml/l liquid organic waste fermented water) gave the best results on the growth of mustard greens (Brassica juncea L.). Keywords: Fermentation water, liquid organic waste, Mustard (Brassica juncea L.)